State-owned enterprises in developed market economies theory and empirics - Del Bo, Chiara; Florio, Massimo 1953-; Frigerio, Marco; Vandone, Daniela (Cambridge University Press, 2025)
After briefly reviewing the received doctrine prior to the waves of privatisations beginning in the 1980s, this Element offers a survey of various analytical frameworks on State Owned Enterprises (SOEs) from the perspective of applied welfare economics. The focus then shifts to a positive analysis of the comparative performance of private versus public enterprises, with a specific emphasis on SOEs in developed market economies over the past two decades; key metrics examined include profitability, productivity, internationalisation, innovativeness, and environmental sustainability. The Element also addresses empirical methodological issues, alongside contextual conditions and institutional factors that help explain the outcomes. It reviews selected contributions from public economics, industrial organisation, corporate governance, management studies and other social sciences. Overall, the Element aims to redefine a neglected research area in public economics, considering the new circumstances of the twenty-first century, where SOEs compete with other firms in developed market economies